Mitigasi Dampak Pandemi COVID-19 melalui Sosialisasi: Laporan KKN Tematik COVID-19 2020 - Cucuk Budiyanto; Ajeng Diah Priasnasari; Nicky Imadudin; Ega Listianingsih (DEDIKASI: Community Service Reports, 2021)
The Rapid spread of Covid-19 has caused worldwide panic due to a high mortality rate. At the beginning of the pandemic, the community did not yet have an adequate understanding of what and how the virus spreads. While tell-tales and social media tend to be discouraging, inaccurate, and fearmongering. The low knowledge and level of public awareness in the face of the outbreak of the Covid-19 pandemic prompted the UNS KKN Team to make socialization a priority for the Covid-19 2020 Thematic Community Service activities. Socialization programs with various strategies were implemented to provide an understanding of PHBS, the importance of using masks, and new behaviors for prevent the spread of the impact of the pandemic more widely in Magelang, Kebumen and Purwokerto areas. The direct face-to-face socialization, posters / banners, or social media posts are considered effective in providing accurate information to the public, as well as clarifying hoax that has spread rapidly to the public regarding the Covid-19 Pandemic.